How ecologists define drought, and why we should do better. (19th July 2019) - Slette, Ingrid J.; Post, Alison K.; Awad, Mai; Even, Trevor; Punzalan, Arianna; Williams, Sere; Smith, Melinda D.; Knapp, Alan K.
Abstract: Drought, widely studied as an important driver of ecosystem dynamics, is predicted to increase in frequency and severity globally. To study drought, ecologists must define or at least operationalize what constitutes a drought. How this is accomplished in practice is unclear, particularly given that climatologists have long struggled to agree on definitions of drought, beyond general variants of "an abnormal deficiency of water." We conducted a literature review of ecological drought studies (564 papers) to assess how ecologists describe and study drought. We found that ecologists characterize drought in a wide variety of ways (reduced precipitation, low soil moisture, reduced streamflow, etc.), but relatively few publications (~32%) explicitly define what are, and are not, drought conditions. More troubling, a surprising number of papers (~30%) simply equated "dry conditions" with "drought" and provided little characterization of the drought conditions studied. For a subset of these, we calculated Standardized Precipitation Evapotranspiration Index values for the reported drought periods. We found that while almost 90% of the studies were conducted under conditions quantifiable as slightly to extremely drier than average, ~50% were within the range of normal climatic variability. We conclude that the current state of the ecological drought literature hinders synthesis and our ability to draw broad ecological inferences because drought is often declared but is not explicitly defined or well characterized. We suggest that future drought publications provide at least one of the following: (a) the climatic context of the drought period based on long‐term records; (b) standardized climatic index values; (c) published metrics from drought‐monitoring organizations; (d) a quantitative definition of what the authors consider to be drought conditions for their system. With more detailed and consistent quantification of drought conditions, comparisons among studies can be more rigorous, increasing our understanding of the ecological effects of drought. Abstract : Drought is a widely studied driver of ecosystem dynamics, but it is unclear how ecologists define or operationalize what constitutes a drought. We reviewed >500 publications and found that ecologists characterize drought in a wide variety of ways, but relatively few publications (~32%) explicitly define drought, and many (~30%) simply equate generally dry conditions with drought and provide little characterization of the conditions studied. This impedes synthesis and, thus, the advancement of ecological understanding. We provide recommendations for describing and quantifying droughts in a way that will facilitate comparisons and strengthen inferences drawn from the collective ecological drought literature. See Letter to the Editor on: https://onlinelibrary.wiley.com/doi/10.1111/gcb.14809 ; See also Response to the Editor on: https://onlinelibrary.wiley.com/doi/10.1111/gcb.14899